2014
DOI: 10.1155/2014/636893
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis as a Risk Factor of Atherosclerosis

Abstract: Over the last two decades, the amount of evidence corroborating an association between dental plaque bacteria and coronary diseases that develop as a result of atherosclerosis has increased. These findings have brought a new aspect to the etiology of the disease. There are several mechanisms by which dental plaque bacteria may initiate or worsen atherosclerotic processes: activation of innate immunity, bacteremia related to dental treatment, and direct involvement of mediators activated by dental plaque and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 91 publications
2
85
1
2
Order By: Relevance
“…There is increasing evidence that oral health impacts on the general well-being of an individual, with cardiovascular disease, diabetes and low birth weight all associated with poor oral hygiene 1–3. Furthermore, poor oral hygiene has been linked with higher incidence of respiratory infections, such as community-acquired pneumonia, healthcare-associated pneumonia, hospital-acquired pneumonia and ventilator-associated pneumonia (VAP) 4–6…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence that oral health impacts on the general well-being of an individual, with cardiovascular disease, diabetes and low birth weight all associated with poor oral hygiene 1–3. Furthermore, poor oral hygiene has been linked with higher incidence of respiratory infections, such as community-acquired pneumonia, healthcare-associated pneumonia, hospital-acquired pneumonia and ventilator-associated pneumonia (VAP) 4–6…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Furthermore, poor oral hygiene has been linked with higher incidence of respiratory infections, such as community-acquired pneumonia, healthcare-associated pneumonia, hospital-acquired pneumonia and ventilator-associated pneumonia (VAP). [4][5][6] Dental plaque is an archetypal biofilm and during critical illness can rapidly become colonised by potential respiratory pathogens and in these cases, it serves as a reservoir for VAP pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…3, 4 The third mechanism is the immune response to the bacteria, which involves the generation of antibodies to bacteria and their toxins, which may have off-target effects in extra-oral tissues (e.g., cross-reactive antibodies that contribute to atherosclerosis). 10 …”
mentioning
confidence: 99%
“…It has been observed that periodontitis is one of the causes or consequences of developing atherosclerosis. Microorganisms or their products present in circulation may promote pathogenesis and enhance local inflammatory changes in vessel walls and thereby may promote process of clotting and clot formation (23). The periodontal disease has also been reported to be an important risk factor for nonhemorrhagic stroke (24).…”
Section: Periodontitis and Bacteremiamentioning
confidence: 99%